Early-Onset Creutzfeldt-Jakob Disease Mimicking Immune-Mediated Encephalitis - Wiels, Wietse A.; Du Four, Stephanie; Seynaeve, Laura; Flamez, Anja; Tousseyn, Thomas; Thal, Dietmar; D’Haeseleer, Miguel (Frontiers in Neurology, 2018)
Objectives: To explore the clinical, radiological, and pathological manifestations of a rare subtype prion disease and their implication for differential diagnosis in case of early-onset neuropsychiatric deterioration. Methods: We discuss a patients’ clinical history, as well as the string of investigations and symptomatological evolution that finally led to a pathological diagnosis. Results: Our patient had the extremely rare VV1 type sporadic Creutzfeldt-Jakob disease. We explain the differential diagnosis of Progressive Encephalomyelitis with Rigidity and Myoclonus and its implications for treatment. Conclusions: Sporadic Creutzfeldt-Jakob disease, especially the VV1 subtype, can present at an early age with an insidious psychiatric onset. Classical findings of prion disease – 14-3-3 protein, PSWC on EEG, and MRI patterns – are not always present. The presence of neural autoantibodies does not always implicate pathogenicity in the presence of other neurological /neurodegenerative conditions.